Investigación a nivel de finca - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1985)
During 1984, intensive on-farm trials were conducted in northern, southern, and central Narino, Colombia, and emphasis was given to the continuation of var. trials and their expansion to determine economic levels and to verification trials. In northern and central Narino, a limited no. of verification trials were planted using the most promising components from 1982B. In both sets of trials, the new agronomic practices offered no yield advantage over farmers' practices. In Antioquia (Colombia), the only technologies to reach verification have been the use of the new line ICA La Selva 1 and the new var. ICA Llanogrande and, in the less developed subzones, increased bean planting density as well. Technology adaptation is not a primary objective of CIAT's participation in on-farm research, although it is achieved indirectly through support given to national programs participating in the network activities. However, the results obtained from on- farm research activities in Colombia show its potential to provide rapid results. (CIAT)